ANALISIS PENGARUH JENIS KELAMIN, TINGKAT SEMESTER DAN MEDIA SOSIAL TERHADAP IPK MAHASISWA DENGAN PENDEKATAN BINARY LOGISTIC REGRESSION: Studi kasus mahasiswa Universitas Bina Bangsa - Sri Sukmawati; Isnaini Mahuda; Ernawati Ernawati; Tubagus Bakhrul Alam (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
Student Grade Point Average (GPA) is a number that shows the achievement or progress of student learning cumulatively from the beginning of the semester to the end. Many things can affect a student's GPA score. This study aims to see the relationship between gender, semester level and student time in using social media on the GPA obtained. The method used is binary logistic analysis (Binary Logistic Regression / BLR) with 1 response variable and 3 predictor variables. The Y categorical data is the GPA of students who are categorized and . Another categorical variability is gender. The conclusions show that student GPA can be explained by variables in the study or student GPA is influenced by gender, semester level and student time in using social media